2022
DOI: 10.1002/jbio.202200059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photobiomodulation in experimental spinal cord injury models: A systematic review

Abstract: This systematic review investigated the repercussions of photobiomodulation using lowlevel laser therapy (LLLT) for the treatment of spinal cord injury (SCI) in experimental models. Studies were identified from relevant databases published between January 2009 and December 2021. Nineteen original articles were selected and 68.4% used light at an infrared wavelength. There was a considerable variation of the power used (from 25 to 200 mW), total application time (8-3000 s) and total energy (0.3-450 J). In 79% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Though there are not many relevant studies, their advantages make this method very promising. Additionally, phototherapy is also a promising strategy for the treatment of SCI [145]. The combination of hydrogels and phototherapy is more effective for treating SCI, because phototherapy could further promote hydrogels to mimic ECM and improve their therapeutic efficacy.…”
Section: Combination Therapymentioning
confidence: 99%
“…Though there are not many relevant studies, their advantages make this method very promising. Additionally, phototherapy is also a promising strategy for the treatment of SCI [145]. The combination of hydrogels and phototherapy is more effective for treating SCI, because phototherapy could further promote hydrogels to mimic ECM and improve their therapeutic efficacy.…”
Section: Combination Therapymentioning
confidence: 99%
“…A literature review conducted by our research group reported the positive effects of local PBM in experimental SCI models employing LLL either alone or in combination with stem cell therapy and the use of anti‐inflammatory drugs. Regardless of the exposure time, application site, wavelength (red or infrared) and other dosimetric parameters, irradiation in continuous or pulsed form led to a reduction in inflammatory markers and the cavity (injury) and promoted axonal growth, the recovery of motor function as well as reductions in hypersensitivity and neuropathic pain 16 …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the exposure time, application site, wavelength (red or infrared) and other dosimetric parameters, irradiation in continuous or pulsed form led to a reduction in inflammatory markers and the cavity (injury) and promoted axonal growth, the recovery of motor function as well as reductions in hypersensitivity and neuropathic pain. 16 Recent clinical trials and experimental studies have demonstrated the auxiliary capacity of PBM in a variety of neurological conditions, such as stroke, 17 traumatic brain injury, 18 neurodegenerative diseases 19 and spinal cord injuries. 20 As there are no effective, completely curative mechanisms for SCI and given the interaction between infrared radiation and biological tissues as well as the painless, noninvasive nature of the method, light therapy could become an important component in the treatment of this clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, LLLT is an effective strategy for promoting neural plasticity and functional recovery in a rat model of SCI. 11 However, few studies have been conducted to determine whether PBMT could be used in the process of inducing NSCs-like neurospheres. Herein, the main purpose of our experiment was to investigate the effects of PBMT on the neural differentiation of DPSCs and the underling mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Andreo et al 10 showed LLLT increased axonal growth, migration and proliferation of Schwann cell. Meanwhile, LLLT is an effective strategy for promoting neural plasticity and functional recovery in a rat model of SCI 11 . However, few studies have been conducted to determine whether PBMT could be used in the process of inducing NSCs‐like neurospheres.…”
Section: Introductionmentioning
confidence: 99%